Openness, imperfect exchange rate pass-through and monetary policy - Frank Smets; Raf Wouters (European Central Bank (ECB), 2002)
This paper analyses the implications of imperfect exchange rate pass-through for optimal monetary policy in a linearised open-economy dynamic general equilibrium model calibrated to euro area data. Imperfect exchange rate pass through is modelled by assuming sticky import price behaviour. The degree of domestic and import price stickiness is estimated by reproducing the empirical identified impulse response of a monetary policy and exchange rate shock conditional on the response of output, net trade and the exchange rate. It is shown that a central bank that wants to minimise the resource costs of staggered price setting will aim at minimising a weighted average of domestic and import price inflation.
Keywords: E58; F41; 330